Building Trust through Strategic Public Relations: The Influence of University Communication on Student Organizations - Daud, Yusri M (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Trust in university administration is a fundamental element in fostering effective higher education governance. However, inadequate communication between university administrators and student organizations often hinders the development of mutual trust. This study aims to examine the influence of Strategic Public Relations (SPR) on Trust toward University Administration (TR) through Communication Quality (CQ) as a mediating variable. A quantitative explanatory survey design was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The population consisted of 93 members of the Student Association of the Islamic Education Management Program (HMP MPI) at the Faculty of Tarbiyah and Teacher Training, UIN Ar-Raniry Banda Aceh. Based on the Krejcie and Morgan sampling table, 76 respondents were selected as the research sample. Data were collected using a four-point Likert-scale questionnaire and analyzed with SmartPLS 4. The findings reveal that Strategic Public Relations positively influences Communication Quality (β = 0.612), Communication Quality positively affects Trust toward University Administration (β = 0.578), and Strategic Public Relations also has a direct positive effect on Trust (β = 0.255). The model demonstrates satisfactory predictive power, with R² values of 0.374 for Communication Quality and 0.651 for Trust, while the SRMR value of 0.056 indicates a good model fit. The study concludes that communication quality serves as the primary mechanism through which strategic public relations enhances students' trust in university administration. Therefore, universities should strengthen transparent, responsive, participatory, and sustainable communication strategies as an integral component of strategic public relations to reinforce institutional trust and stakeholder relationships.